Pulmonary Arterious Malformation as Rare Cause of ST-Segment Elevation Myocardial Infarction - Daniel Knuchel, MSc; Daniel Jauslin, MD; Christian Maurer, MD (JACC: Case Reports)
Background: Pulmonary arteriovenous malformation (PAVM) is a rare shunt between the arteries and veins of the lungs, which can lead to paradoxical embolism. It is mostly caused by an autosomal-dominant disorder called hereditary hemorrhagic telangiectasia. Case Summary: A 62-year-old woman presented with acute chest pain, initially diagnosed as ST-segment elevation myocardial infarction. Further investigation revealed myocardial infarction with nonobstructive coronary arteries (MINOCA) caused by a PAVM. It was successfully embolized with an Amplatzer device. Discussion: Multimodality imaging is the cornerstone of the differential diagnosis of MINOCA, a conglomerate of rare causes of myocardial infarction. In our case, we identified PAVM as the cause of myocardial infarction due to paradoxical embolism. Due to its high morbidity, mainly due to the increased risk of stroke, early diagnosis and treatment of PAVM is important for patient outcome. Take-Home Message: This case highlights the importance of multimodality imaging in the diagnosis of MINOCA.